Through the Looking Glass : China's Foreign Journalists from Opium Wars to Mao - French, Paul, 1966- (Book collections on Project MUSE., 2009)
The convulsive history of foreign journalists in China starts with newspapers printed in the European factories of Canton in the 1820s. It also starts with a duel between two editors over the future of China and ends with a fistfight in Shanghai over the revolution. This book tells the story of China's foreign journalists.